Cybersecurity-Focused Modeling of Computer Virus Propagation Incorporating Removable Media (European Journal of Pure and Applied Mathematics, 2025)
The persistent threat of malware propagation necessitates advanced modeling techniques to develop proactive cybersecurity defenses. While numerous epidemiological models exist for network-based spread, the critical role of removable media as a potent transmission vector remains quantitatively under explored. This paper introduces a novel six compartment SLAQRD model that synthesizes both network and removable media infection routes, incorporating realistic states such as Latent, Active, Quarantined, Recovered, and Deactivated systems. A rigorous mathematical analysis establishes the model's well-posedness and derives a key epidemiological threshold governing outbreak dynamics. Furthermore, the global stability of the disease-free equilibrium is proven under specific conditions. To transition from theory to actionable policy, an optimal control framework is formulated, dynamically allocating resources to media protection, quarantine, and recovery efforts. Numerical simulations demonstrate that this optimized strategy significantly mitigates outbreak impact, reducing peak infections by 35.7% and system deactivation by 45.8%, while increasing recovered systems by 62.5%. The study provides a quantitative foundation for resource allocation, emphasizing that investments in proactive detection and rapid containment are paramount for enhancing organizational cybersecurity resilience.
Keywords: Cybersecurity; Malware Propagation; Removable Media; Optimal Control; Resource Allocation